IDENTIFICATION OF NEW MOLECULAR BIOMARKERS - PROTEOMICS - Sladjana Vujacic (Sanamed, 2018)
The pathogenesis of the tumor is extremely complex and can not be fully explained by the existing methodological approaches. Proteomics is an interdisciplinary science that deals with the study of proteins, carriers of the biological functions of the organism. It encompasses a series of methods for protein analysis and provides exceptional possibilities for understanding the molecular basis of the disease, the possibilities of early diagnosis, and the production of new drugs. Proteomic analyzes of the malignancy altered tissue have revealed proteins involved in the progression of the disease, and thus contributed to the discovery of potential drug treatment methods. Proteomics provides a better understanding of the molecular basis of these diseases, plays a role in the diagnosis of the same, and it is expected to make a significant contribution to the development of new more effective drugs and the development of personalized therapy